Peripherally inserted central catheter insertion and management in Hodgkin and non-Hodgkin lymphomas: a 13-year monocentric experience - Derudas, Daniele; Massidda, Stefania; Simula, Maria Pina; Dessì, Daniela; Usai, Sara Veronica; Longhitano, Giuseppe; Ibba, Daniela; Aracu, Loredana; Atzori, Monica; La Nasa, Giorgio (Frontiers in Hematology, 2023)
Background: Non-Hodgkin's lymphomas (NHLs) and Hodgkin's lymphoma (HL) are two of the most common hematologic diseases that require infusion of immunochemotherapies in conjunction with radiotherapy, often in an outpatient setting. For relapsed/refractory disease, autologous peripheral hematopoietic stem cell transplantation and sometimes allogeneic transplantation (HSCT) are considered standard treatment options. Recently, Chimeric Antigen Receptor (CAR) T cells and bispecific antibodies have emerged as an important and effective option for the treatment of relapsed/refractory patients. These medical approaches deserve effective, safe, and durable vascular access, especially for the ambulatory population undergoing discontinuous treatment associated with high rates of complications and life-threatening toxicities. Peripherally inserted central catheters (PICCs) are vascular devices with an intermediate-to long-term lifespan that are inserted ultrasonically into a peripheral brachial vein. Their ease of insertion by trained nurses and low rate of catheter-related infectious and thrombotic complications make them ideal devices for the treatment of oncology and hematology patients. Purpose: In this study, we aim to demonstrate that PICCs are an essential tool for the treatment of HL and NHLs patients in terms of efficiency and safety Methods and Results: From March 2007 to June 2020, 316 PICC implantations were performed by oru PICC team in 276 HL patients and 363 PICC in 322 NHLs patients. The total duration of PICC life was 50660 days in HL and 43919 days in NHLs patients. Most PICCs were removed at the end of therapy, and the rate of mechanical complications was low. Only 1 and 4 episodes of confirmed PICC-related CRBSI (0.3%; 0.02/1000 days/PICC and 1.2%; 0.07/1000 days/PICC) were recorded in HL and NHL patients, respectively. There were only 11 (3.6%; 0.25/1000 days/PICC) and 9 (2.6%; 0.17/1000 days/PICC) episodes of symptomatic PICC-related thrombotic complications in HL and NHL patients, respectively, without removal. Conclusions: Our data indicate that the use of PICC can be considered the device of choice in the treatment of HL and NHLs patients because it is easy to insert, safe to use, long lasting, and has a low complication rate, especially in the outpatient setting.